CEO overseas experience, cultural distance and corporate financialization: the mediating effect of ESG investment in China - Zheng, Minyu; Mohd Nor, Normaziah; Mohd Ashhari, Zariyawati (Human Resources Management Academic Research Society (HRMARS), 2024)
Recently, Chief Executive Officers (CEOs) with overseas experiences show the “star effect”, according to upper echelons theory, CEOs’ overseas experiences might relate to corporate financialization, but there is little evidence of whether and how overseas CEOs affect it. Given the increasing trend of hiring overseas CEO in China, the study fills in the gap in the literature by examining the effect of CEOs with overseas experiences on corporate financialization. This study utilizes balanced panel data from 1,213 listed companies on the China A-share market between 2012 and 2022, resulting in a dataset comprising 13,343 observations. After employing both a two-way fixed effects model and a SYS-GMM model, the finding reveals that CEOs with overseas experience tend to inhibit corporate financialization. The finding remains robust after a series of tests, including the use of different models (OLS, FE with provincial effects), adjustments to the measurement of independent and dependent variables, and consideration of the impact of COVID-19 (excluding data from 2020 and 2022). To address the endogeneity issue, this study employs a two-way fixed effect regression by lagging variables, Two-Stage Least Squares (2SLS), Heckman two-stage regression, and the propensity score matching (PSM). The results remain robust and reliable. Moreover, overseas CEOs primarily inhibit corporate financialization by improving ESG investment. Furthermore, the cultural distance between the host countries where CEO worked or received education and China inhibits corporate financialization, especially, Individualism vs Collectivism (IC) distance makes the most significant contribution. This study reveals how CEOs with overseas experience influence corporate financialization strategies, providing key insights for optimizing corporate governance and effectively leveraging executives' international perspectives. The findings suggest that companies should value cross-cultural experience in the context of globalization to better navigate its challenges. Future research could further explore the impact of cross-cultural experience on financialization strategies amid digital transformation and sustainable development trends.